Phosphorus use efficiency in 10 common bean genotypes (Phaseolus vulgaris L.) - Gómez, Luis A.; Vadez, Vincent; Hernández, Germán; Sánchez, Tamara; Toscano, Vidalina (Agronomía Mesoamericana, 2016)
Ten common bean genotypes (Jamapa, APN18, Carioca, Río Tibají, Porrillo, Pot 51, Bat 271, Bolita 42, Calima y CC25-9N) were grown in an intensively aereated nutritive solution with 5 weekly doses of phosphorus (0; 62,5; 125; 187,5 and 1875 mM/plant) and 2 mM of N in the form of KNO3. The objective was to evaluatefoliar biomass and its P content, as well as, to calculate the P Use Efficiency (PUE) parameter based on these and relate them with the concentration levels with which plants were nourished. The optimum requirement level obtained fromboth biomass and PUE criteria ranged between 62,5 - 187,5 mM/plant/week; this supported differences for P nutrition within the genera. Pot 51 showed the lowest requirement and Carioca the highest for optimum yielding; but Bat 271 exhibited the highest efficiency index even at a suboptimum level. Among these genotypes, CC25-9N showed the lowest efficiency and Porrillo showed no variation for this parameter. It may be concluded that the highest efficiency point coincided in 80 % of the cases with the maximum biomass production point.